2018
DOI: 10.1038/s41598-018-28537-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative and phylogenetic analysis of a novel family of Enterobacteriaceae-associated genomic islands that share a conserved excision/integration module

Abstract: Genomic Islands (GIs) are DNA regions acquired through horizontal gene transfer that encode advantageous traits for bacteria. Many GIs harbor genes that encode the molecular machinery required for their excision from the bacterial chromosome. Notably, the excision/integration dynamics of GIs may modulate the virulence of some pathogens. Here, we report a novel family of GIs found in plant and animal Enterobacteriaceae pathogens that share genes with those found in ROD21, a pathogenicity island whose excision i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(51 citation statements)
references
References 66 publications
2
39
0
Order By: Relevance
“…Several members of Enterobacteriaceae family have on their chromosome a type of excisable PAIs denominated ROD21-like islands [26,27]. This is the case of Salmonella sp (ROD21 and SPI-7) [23], Escherichia coli UPEC (PAI I536, PAI II536, and PAI V536) [36], Klebsiella pneumoniae (GIE492) [37], Vibrio cholera (VPI-2 VSP-I and VSP-I) [38], and Pectobacterium atrosepticum (HAI2) [39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several members of Enterobacteriaceae family have on their chromosome a type of excisable PAIs denominated ROD21-like islands [26,27]. This is the case of Salmonella sp (ROD21 and SPI-7) [23], Escherichia coli UPEC (PAI I536, PAI II536, and PAI V536) [36], Klebsiella pneumoniae (GIE492) [37], Vibrio cholera (VPI-2 VSP-I and VSP-I) [38], and Pectobacterium atrosepticum (HAI2) [39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with S. Enteritidis-ΔDRSΔint have suggested that the impairment of ROD21 excision can modulate the expression of genes within ROD21 [27]. Therefore, we evaluated whether S. Enteritidis-ΔintΔrdf strain also showed an altered gene expression, equivalent to S. Enteritidis-ΔDRSΔint, and whether impairment of ROD21 excision affects the transcription of genes within ROD21 and genes in other pathogenicity islands that are required for invasion of epithelial cells and the establishment of a systemic infection in mice.…”
Section: Rod21 Excision Modulates the Expression Of Virulence Genes Imentioning
confidence: 98%
See 2 more Smart Citations
“…These regions may encode numerous beneficial traits for bacteria and thus have an influence on better adaptation of microorganisms to changing environmental conditions. Due to the gene content, these regions can be divided into pathogenicity, metabolic, fitness, symbiosis and resistance islands and can be distinguished from the host genome based on different nucleotide compositions, including IS fragments, anomalous GC content, transposons and tRNA genes 37,38 . To evaluate the genetic diversity of E. aerogenes LU2, the presence of GIs acquired through HGT was identified using the IslandViewer 4 platform and the IslandPath-DIMOB, SIGI-HMM, and IslandPick prediction methods (Additional file 1) 39 .…”
Section: Bacteriocin Biosynthesismentioning
confidence: 99%